1999
DOI: 10.1159/000006957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Losartan Titrated to Losartan/Hydrochlorothiazide and Amlodipine on Left Ventricular Mass in Patients with Mild-to-Moderate Hypertension

Abstract: To study the effects of the angiotensin II receptor antagonist Losartan and Amlodipine on left ventricular mass (LVM), we performed blood pressure measurements and transthoracic echocardiographies at baseline. After a 4-week placebo run-in period, 25 patients with mild-to-moderate essential hypertension were randomly allocated to active treatment with Losartan 50 mg titrated to Losartan 50 mg/hydrochlorothiazide (HCT) 12.5 mg (n = 11) or Amlodipine 5 mg titrated to 10 mg (n = 14) for 16 weeks. After treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
1
24
2
Order By: Relevance
“…This is also the first randomized trial on reduction of LVM by telmisartan in human hypertensives. LVM reduction in other studies on ARBs [2,3,6] was greater in comparison to the LVM reduction in our study. In contrast to other studies that included only patients with echocardiographic [6], ECG LVH [1] or with a higher prevalence and severity of LVH [2,3], we studied general medical outpatients with newly detected hypertension with a lower prevalence of LVH (30%) and a lower baseline LVM.…”
contrasting
confidence: 90%
See 1 more Smart Citation
“…This is also the first randomized trial on reduction of LVM by telmisartan in human hypertensives. LVM reduction in other studies on ARBs [2,3,6] was greater in comparison to the LVM reduction in our study. In contrast to other studies that included only patients with echocardiographic [6], ECG LVH [1] or with a higher prevalence and severity of LVH [2,3], we studied general medical outpatients with newly detected hypertension with a lower prevalence of LVH (30%) and a lower baseline LVM.…”
contrasting
confidence: 90%
“…Losartan significantly reduces left ventricular mass (LVM) [1][2][3] but has a limited duration of action and a small distribution volume. This may limit the effectiveness of losartan in reducing LVM.…”
mentioning
confidence: 99%
“…Both electrophysiological and structural remodeling contributes to maintaining the arrhythmia in LVH. 13,33 In our experimental model with TAC, we observed that chronic treatment with candesartan did normalize several electrophysiological parameters such as PR interval, ERP-AVN, SNRT, CSNRT AV-WPCL and VA-WPCL (Table 3). The TAC procedure also prolonged ERP-RV, and candesartan returned this value to the control level, although there was no statistical significance.…”
Section: Discussionmentioning
confidence: 82%
“…Martina et al, 26 in patients with mild-to-moderate hypertension reported that losartan 50 mg/hydrochlorothiazide 12.5 mg significantly reduced LVM after 16 weeks of treatment, whereas the reduction in LVM seen in the amlodipine group was not significantly different. Kanno et al, 27 in 24 diabetic patients with end-stage renal disease reported that losartan decreased LVM index, posterior wall thickness, and intraventricular wall thickness in spite of a similar reduction of blood pressure in patients receiving placebo; and this effect was observed since 4 months of treatment.…”
Section: Discussionmentioning
confidence: 94%